LncRNA PITPNA-AS1 as a Potential Diagnostic Marker and Therapeutic Target Promotes Hepatocellular Carcinoma Progression via Modulating miR-448/ROCK1 Axis - Wang, Qing-fang; Wang, Qing-lin; Cao, Ming-bo (Frontiers in Medicine, 2021)
Background: Long non-coding RNAs are critical to hepatocellular carcinoma (HCC) developments. LncRNA PITPNA antisense RNA 1 (PITPNA-AS1) is a new regulator in several tumors. However, the mechanism by which PITPNA-AS1 mediates the tumorigenesis of HCC remains unclear. Methods: RT-qPCR was used to detect the level of PITPNA-AS1 in HCC specimens and cells. The biological functions of PITPNA-AS1 were explored by several functional experiments in vivo and in vitro. Luciferase reporter assays and Chromatin immunoprecipitation (ChIP) assays were applied for exploring whether E2F1 was capable of binding to PITPNA-AS1 promoter area. The binding relationship among PITPNA-AS1, miR-448 and ROCK1 were studied by Luciferase assay and pull-down assays. Results: We found that PITPNA-AS1 expressions were distinctly upregulated in both HCC specimens and cell lines. High PITPNA-AS1 levels were an unfavorable biomarker for patients with HCC. Additionally, E2F1 could activate the transcription of PITPNA-AS1. Functionally, knockdown of PITPNA-AS1 suppressed the proliferation, migration and invasion of HCC cells. Mechanistically, PITPNA-AS1 functioned as competing endogenous RNA to increase ROCK1 expressions via sponging miR-448. Conclusion: The newly identified E2F1/PITPNA-AS/miR-448/ROCK1 axis promoted the oncogenicity of HCC cells. This novel axis is likely to be a promising HCC therapeutic aim.